Determing the level of physical fitness of future electrical engineers of railway transport - Єфремова (Yefremova A.) А. Я. (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The article considers the question about the level of physical fitness of “Automation, Remote Control and Communication” Department of UkrGAZhT students. Here is also presented the results of test on physical fitness of first-year students (future electrical engineers of railway transport). The obtained results of research provide an opportunity to optimize students’ physical preparation and recommend exercises for developing certain physical characteristics and thereby increase the level of first-year students’ physical fitness. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>